Implementation of product sharing and search system on mobile platform (Part-II) - Manjunath, Manmitha. (2013)
Online sites which leverage on user participation and community have grown over the years. These sites focus on identifying something that people find interesting and they create a platform that helps connect these people together and build a community. These websites have corresponding mobile applications which also have a similar interface, resulting in a cohesive user experience for the user. In addition, they integrate seamlessly with social media to ensure content can shared via social media just as easily.